Advances in accounting education teaching and curriculum innovations - Catanach, Anthony H.; Feldmann, Dorothy (Bingley, U.K. : Emerald, 2011)
Advances in Accounting Education: Teaching and Curriculum Innovations is a refereed, academic research annual that aims to meet the needs of faculty members interested in ways to improve their classroom instruction. It includes both non-empirical and empirical articles dealing with accounting pedagogy at college and university level. Non-empirical papers are academically rigorous and specifically discuss the institutional context of a course or program, as well as any relevant trade offs or policy issues. Empirical reports exhibit sound research design and execution, and develop a thorough motivation and literature review. Thoughtful, well-developed articles describe how teaching methods or curricula/programs can be improved. Advances in Accounting Education: Teaching and Curriculum Innovations serves as a forum for sharing generalizable teaching approaches ranging from curricula development to content delivery techniques. Readable, relevant and reliable this volume is of interest to all instructors, researchers and administrators committed to improving accounting education at the college and university level. This volume presents relevant, readable articles dealing with accounting pedagogy at college/university level. It serves as a forum for sharing generalizable teaching approaches ranging from curricula development to content delivery techniques and is of interest to instructors, researchers and administrators committed to improving accounting education.
The UCare business plan project : a managerial accounting classroom teaching tool / Linda Matuszewski, Fabienne Miller -- Backpack to briefcase : the transformation from student to accounting professional / Gia Chevis, Charles E. Davis, R. Kathy Hurtt -- Ethical leaders in accounting / Patrick T. Kelly, Christine E. Earley -- The usefulness and interactions of WebCT from an accounting student's perspective / Abdel K. Halabi, Paul De Lange -- A note on teaching the effective interest method related problems in accounting / Avinash Arya -- Performance predictors in a graduate accounting program / Elizabeth V. Grace, Thomas G. Black -- Online versus traditional accounting degrees : perceptions of public accounting professionals / James M. Kohlmeyer, Larry P. Seese, Terry Sincich -- Effects of converting student evaluations of teaching from paper to online administration / Sharon M. Bruns, Timothy J. Rupert, Yue (May) Zhang.
Mode of access: World Wide Web.
Keywords: Accounting -- Study and teaching